Secure and efficient cloudlet networks: blockchain integration with agent-based proof of trust mechanism - Nothile C. Masango; Jeffrey O. Agushaka; Mercy C. Amaefule; Olutosin Taiwo; Peiying Zhang; Absalom E. Ezugwu; Kashif Saleem; Aseel Smerat; Laith Abualigah (EURASIP Journal on Wireless Communications and Networking)
Abstract Data security in mobile environments has become a critical concern, driven by the growing demand for mobile services and the proliferation of data-intensive applications such as online gaming, virtual reality, and augmented reality. These applications generate massive amounts of data, challenging the storage, computational capacity, and battery life of mobile devices. Cloud environments offer a solution through task offloading, but centralized architectures introduce latency and potential vulnerabilities. Edge computing-based cloudlet networks have emerged as a promising alternative, providing localized resources to enhance service quality. However, their proximity to users increases susceptibility to security threats, posing barriers to widespread adoption. This paper presents a novel approach to addressing these challenges by integrating blockchain technology with cloudlet networks, bolstered by an agent-layer concept. The proposed architecture features an agent between mobile devices and cloudlets, utilizing a unique "proof of trust" consensus mechanism. This mechanism evaluates trust and experience based on the number of coins held by nodes, selecting miners for message verification using an elliptic curve cryptography scheme. In cases of dispute, a third miner resolves conflicts, with incorrect verifications resulting in penalties that deter malicious behavior. Experimental results demonstrate that this solution significantly enhances security, mitigates latency, and improves network performance compared to existing methods. These findings highlight the potential of blockchain-integrated cloudlet networks to revolutionize mobile data processing, offering robust security and reliable interactions between mobile devices and cloudlets.